2015
DOI: 10.1111/asj.12429
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of milk with and without solid feed during the monogastric phase: Effect on fibrolytic and methanogenic microorganisms in the gastrointestinal tract of calves

Abstract: Microbial communities are affected by diet and play a role in the successful transition from milk to a solid diet. The response of microorganisms in the gastrointestinal tract of Holstein bull calves to the uptake of milk with solid feed (control treatment; CT), or milk without solid feed (milk-only treatment; MT) during the first 3 weeks of life was investigated. Samples were collected from the rumen (fluid and tissue), abomasum (fluid), cecum (fluid and tissue) and feces at 7, 14 and 20 days of age. Calf wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 58 publications
1
23
0
1
Order By: Relevance
“…Methanomethylophilus alvus ), bacteria known to occupy different metabolic niches ( Bacteroides, Butyrivibrio, Lactobacillus, Megasphaera, Prevotella, Ruminococcus, Streptococcus ) and anaerobic fungi with known prominent roles in fiber degradation ( Caecomyces, Orpinomyces , SK3). These results show that colonization of archaeal, bacterial, and fungal communities occur prior to the introduction of solid food (Bryant et al, 1958 ; Fonty et al, 1987 ; Rey et al, 2014 ; Guzman et al, 2016 ) and supports the suggestion that microbiota-related interventions could be viable right after birth (Abecia et al, 2013 ).…”
Section: Discussionsupporting
confidence: 67%
“…Methanomethylophilus alvus ), bacteria known to occupy different metabolic niches ( Bacteroides, Butyrivibrio, Lactobacillus, Megasphaera, Prevotella, Ruminococcus, Streptococcus ) and anaerobic fungi with known prominent roles in fiber degradation ( Caecomyces, Orpinomyces , SK3). These results show that colonization of archaeal, bacterial, and fungal communities occur prior to the introduction of solid food (Bryant et al, 1958 ; Fonty et al, 1987 ; Rey et al, 2014 ; Guzman et al, 2016 ) and supports the suggestion that microbiota-related interventions could be viable right after birth (Abecia et al, 2013 ).…”
Section: Discussionsupporting
confidence: 67%
“…Apart from the change of diet structure and components, weaning also involves both psychological and physiological stress as the kids were no longer raised together with the dams 45, 46 . However, as a strategy to adapt the suckling ruminants to a diet composed of forage and concentrates and reduce the cost of production, early weaning has been studied intensively and regarded as an effective approach in manipulating the microbial community and improving rumen fermentation 9, 47 . It was also revealed in the PCoA analysis that the methanogen community in RE was distinct from those in the other fractions for most of the time throughout rumen development, as supported by previous studies which reported differences between the epithelial tissue-associated and the rumen contents-associated bacterial communities 29, 48 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the GIT microbiota may be amenable to alterations that will have long-lasting impacts in the adult cow. However, analysis of the calf GIT microbiota has been limited to primarily the rumen, and previous work on other sections of the GIT has either pooled samples (18) or targeted specific bacterial species (19). This prevents capture of interanimal variation and provides a restricted picture of the bacterial diversity in the calf GIT.…”
Section: Importancementioning
confidence: 99%